PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP SUMBER- SUMBER AJARAN ISLAM PADA SISWA KELAS V SD - Putri, Anggina Hasanah; Nurmayani, Nurmayani; Anandhita, Vini; Chaniago, Sakira Azzura; Natasya, Feby; Nurmaini, Alya (Universitas Negeri Medan, 2025)
Islamic Religious Education (IRE) is an important component in shaping the character, morals, and spirituality of students from elementary school age onwards. This study seeks to examine the extent to which PAI learning influences fifth-grade elementary school students' knowledge of Islamic teachings, including the Qur'an, Hadith, Ijma', and Qiyas. The study was conducted at SD IT Al-Hijrah, Deli Serdang Regency, North Sumatra Province, using a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation with fifth-grade teachers as the main informants. The results showed that PAI learning was quite successful in instilling students' understanding of the Qur'an and Hadith, and some of the students' daily practices even reflected the application of these values. However, the material on Ijma' and Qiyas was still limited to basic introduction and had not been studied in depth. Teachers play a major role in guiding students through various methods, setting a good example, and encouraging religious practices at school. However, there are several obstacles, including a homogeneous learning environment and limited use of digital learning media. Overall, PAI learning has been proven to have a positive effect on improving students' knowledge, although innovation is still needed to better suit the needs of the times.